2011
DOI: 10.1093/ecam/nep113
|View full text |Cite
|
Sign up to set email alerts
|

The Ayurveda Education in India: How Well Are the Graduates Exposed to Basic Clinical Skills?

Abstract: “Ayurveda” is an ancient system of healthcare that is native to India. At present, in India, there are more than 240 colleges that offer a graduate-level degree (Bachelor of Ayurvedic Medicine and Surgery—BAMS) in Ayurveda. Even though the Central Council of Indian Medicine, the governing body that monitors the matters related to Ayurveda education, has imposed various educational norms and regulations, the standard of education has been a cause of concern in recent years. The mushrooming of substandard Ayurve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 12 publications
(9 reference statements)
0
44
0
Order By: Relevance
“…This questionnaire is designed on the basis of the explanation found in Charaka Samhita , one of the most authentic textbooks on Ayurveda, authored around 1000 years BC [20]. This explanation is, in turn, based on the specific attribute (Guna) of a particular Dosha [5] .…”
Section: Methodsmentioning
confidence: 99%
“…This questionnaire is designed on the basis of the explanation found in Charaka Samhita , one of the most authentic textbooks on Ayurveda, authored around 1000 years BC [20]. This explanation is, in turn, based on the specific attribute (Guna) of a particular Dosha [5] .…”
Section: Methodsmentioning
confidence: 99%
“…[5] In addition, our study also showed that graduates are not trained sufficiently in handling clinical emergencies at primary healthcare level through Ayurveda. In general, we concluded that the exposure to basic clinical skills is insufficient during graduate programs.…”
Section: Results Of a Nationwide Surveymentioning
confidence: 89%
“…However, there needs to be integration at some level between BM and TM curricula to enable integrated therapy for patient-oriented treatment. This model is followed in countries like China and Vietnam, where both streams of medical education are integrated at all levels 6 . At present nothing about TM is included in BM curriculum due to its non-acceptance by the Indian Medical Council, the statutory body for BM education.…”
Section: Educationmentioning
confidence: 99%